Response to mild water stress in transgenic Pssu-ipt tobacco - Synková, Helena; Valcke, Roland (Physiologia plantarum, 2001)
The response of antioxidant enzymes to cyclic drought was studied in control non-transformed tobacco (Nicotiana tabacum L. cv. Petit Havana SR1) and two types of transgenic Pssu-ipt tobacco (grafted on wild rootstock and poorly rooted progeny of F1 generation) grown under different conditions of irradiation (greenhouse, referred as high light, versus growth chamber, referred as low light). Water stress cycles started with plants at two contrasting developmental stages, i.e., at the stage of vegetative growth (young) and at the onset of flowering (old). Drought reduced the growth of SR1 plants compared with transgenic ones, particularly, when treatment started in earlier stage of plant development. Relative leaf water content was significantly lower (below 70%) in all transgenic grafts and plants compared with the wild type, irrespective of age, drought, and growth conditions. The response of antioxidant enzymes was significantly dependent on plant type and plant age; nevertheless, growth conditions and water stress also affected enzyme activities. Contrary to non-transgenic tobacco, where about half of glutathione reductase activity was found in older plants, both transgenic types exhibited unchanged activities throughout plant development and stress treatment. No differences were found in catalase activity, although the growth in the greenhouse caused a moderate increase in all older plants. In contrast to non-transgenic and Pssu-ipt rooted plants, peroxidase activities (ascorbate, guaiacol, and syringaldazine peroxidase) in older Pssu-ipt grafts were up to four times higher, irrespective of growth and stress, nevertheless, the effect seemed to be age-dependent. Superoxide dismutase (SOD) activity was affected particularly by plant age but also by growth conditions. Unlike in older plants, water stress caused an increase of SOD activities in all younger plants. The differences observed in activities of enzymes of intermediary metabolism (i.e., malic enzyme and glucose-6-phosphate dehydrogenase) revealed that transgenic grafts probably compensated differently for a decrease of ATP and NADPH than control and transgenic rooted plants under stress.